Proceedings of the 45th ACM Technical Symposium on Computer Science Education 2014
DOI: 10.1145/2538862.2538938
|View full text |Cite
|
Sign up to set email alerts
|

Challenging stereotypes and changing attitudes

Abstract: Computer programming is now used broadly across many industries, with a diversity of working adults writing programs and interacting with code as part of their jobs. However, negative attitudes toward programming continue to deter many from studying computer science and pursuing careers in technology. To begin understanding adults' attitudes toward computer programming and how we can improve them, we used an educational video game to give 200 adult participants a concrete programming experience via the web, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(8 citation statements)
references
References 29 publications
2
5
1
Order By: Relevance
“…We were not able to replicate the findings of a recent study which revealed significant differences in attitude between male and female students (Sun et al, 2022). However, several other studies have found no gender difference in programming attitude (Amnouychokanant et al, 2021;Charters et al, 2014;Gul et al, 2022;Ozdemir et al, 2020) or no significant predictive effect of gender on attitude (Gurer et al, 2019). This finding suggests that rather than employing individualised instructions that would meet the learning needs of a particular gender category, attention should be on employing more holistic approaches that eliminate programming difficulty and encourage positive attitudes toward programming.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We were not able to replicate the findings of a recent study which revealed significant differences in attitude between male and female students (Sun et al, 2022). However, several other studies have found no gender difference in programming attitude (Amnouychokanant et al, 2021;Charters et al, 2014;Gul et al, 2022;Ozdemir et al, 2020) or no significant predictive effect of gender on attitude (Gurer et al, 2019). This finding suggests that rather than employing individualised instructions that would meet the learning needs of a particular gender category, attention should be on employing more holistic approaches that eliminate programming difficulty and encourage positive attitudes toward programming.…”
Section: Discussioncontrasting
confidence: 99%
“…We argue that experienced programmers are more likely to have positive attitude judgement compared to freshmen. The explanation to justify our argument is based on previous studies (Charters et al, 2014;Cheah, 2020). These studies infer that novice programmers often develop negative attitudes at the initial stage, but the attitude reduces as the students attend more programming lectures and solve more programming problems.…”
Section: Discussionmentioning
confidence: 89%
“…It was nice to look at programming as a series of puzzles rather than a complex language." These results support H1 and those in Charters et al (2014), which found significant attitude improvement regardless of gender and education level after a brief online programming experience.…”
Section: Motivationsupporting
confidence: 86%
“…It is based around use of IT, on the assumption that all respondents would use IT to some degree. It is recognized from literature [18,32,40,80] and our practice that nowadays programs are wrien by specialists in other domains who do not identify themselves as programmers and may not have ever been in a programming class. Dorn et al [24] (p.30) report of the projects completed by end-users that "the projects were typical of what one might expect from a novice programmer".…”
Section: Methodology 31 E Surveymentioning
confidence: 99%